2020
DOI: 10.1016/j.gpb.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effects of Gegen Qinlian Decoction via the Gut Microbiota are Attributable to Its Key Ingredient Berberine

Abstract: Gegen Qinlian Decoction (GQD), a traditional Chinese medicine (TCM) formula, has long been used for the treatment of common metabolic diseases, including type 2 diabetes mellitus . However, the main limitation of its wider application is ingredient complexity of this formula. Thus, it is critically important to identify the major active ingredients of GQD and to illustrate mechanisms underlying its action. Here, we compared the effects of GQD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 64 publications
0
59
0
Order By: Relevance
“…Knocking down Aim2 and NLRP3 can alleviate renal fibrosis, inflammation, and injury (Kopalli et al, 2016;Cao et al, 2021). In clinical settings, GGQLD has frequently been adopted for the treatment of diabetes and UC (Xu et al, 2011;Zhao et al, 2020). GGQLD has been suggested to suppress the inflammatory signal transduction pathway and promote the antioxidant effect, thus improving UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knocking down Aim2 and NLRP3 can alleviate renal fibrosis, inflammation, and injury (Kopalli et al, 2016;Cao et al, 2021). In clinical settings, GGQLD has frequently been adopted for the treatment of diabetes and UC (Xu et al, 2011;Zhao et al, 2020). GGQLD has been suggested to suppress the inflammatory signal transduction pathway and promote the antioxidant effect, thus improving UC.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in vitro and in vivo suggest that some active ingredients in GGQLD, like berberine, baicalin, and puerarin, obviously mitigate oxidative stress (OS) and inflammation (Dinesh and Rasool, 2017;Guarino et al, 2017;Yu et al, 2021). We previously discovered that GGQLD exerted diabetes-mitigating (Xu et al, 2011;Li et al, 2013;Zhang et al, 2013) and anti-inflammation effects through its active ingredients (Tian et al, 2013;Ryuk et al, 2017;Wu et al, 2019). Besides, inflammatory response, lipid, and glucose metabolic disorders are also important for HUA.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, puerarin, baicalin, baicalein, wogonin, berberine, and ammonium glycyrrhizinate could improve insulin resistance and also have good therapeutic effects on cardiovascular disease, diabetic nephropathy, diabetic retinopathy, and other complications caused by diabetes [ 8 17 ]. In animal experiments, studies have confirmed that GQD can play a role in the treatment of T2DM from regulating glucose and lipid metabolism, reducing oxidative stress response, changing the structure of intestinal flora, reducing the expression levels of inflammatory factors, and improving insulin resistance [ 7 , 18 , 19 ]. However, further elucidation of its possible molecular mechanism is still of great significance for the discovery and clinical application of monomer drugs of GQD.…”
Section: Introductionmentioning
confidence: 99%
“…Both treatments significantly changed the overall structure of the gut microbiota in a diabetic rat model and enriched butyrateproducing bacteria, such as Faecalibacterium and Roseburia, accompanied by significantly elevated SCFA levels in rat feces. This alleviated intestinal inflammation and lowered blood glucose (Xu et al, 2020). In addition, BBR and metformin have similar hypoglycemic effects.…”
Section: Antidiabetic Effects Of Berberine By Regulating Gut Microbiota-dependent Metabolitesmentioning
confidence: 85%